Model kepemimpinan transformasional dalam manajemen pembiayaan sekolah - Heru Ady Prasetyo; Ngurah Ayu Nyoman M.; Endang Wuryandini (Indonesian Journal of Educational Development, 2021)
This study aims to produce a transformational leadership model design in school financing management. This type of research is Research and Development with 4D steps (Define, Design, Development and Dissemination). The technique of collecting data from interviews, observations, documentation is concluded as factual designs. The development stage of designing a transformational leadership model in school financing management is validated by educational experts and practitioners through Focus Group Discussions (FGD), into internal tested product designs not field tested. The results of preliminary research obtained visualization of the factual model of Top Down leadership in school financing management. The development stage obtained the results of the visualization of transformational leadership models in school financing management. The results of the validation and assessment of the two education experts (FGD) obtained a value of 46 percent of 95.83% of the interpretation of "very feasible", while the results of the validation and assessment of five education practitioners obtained a score of 101 percentage of 84.16% of the interpretation of "very feasible". So Expert 1 and Expert 2 agree that a transformational leadership model in school financing management is “very feasible” and tested. The principal should implement a transformational leadership model in school financing management so that the principles of participation, transparency and accountability are implemented. Penelitian ini bertujuan menghasilkan rancangan model kepemimpinan transformasional dalam manajemen pembiayaan sekolah. Jenis penelitian Research and Development dengan langkah 4D (Define, Design, Development and Dissemination). Teknik pengumpulan data wawancara, observasi, dokumentasi disimpulkan sebagai desain faktual. Tahap pengembangan merancang model kepemimpinan transformasional dalam manajemen pembiayaan sekolah divalidasi pakar dan praktisi pendidikan melalui Focus Group Discussion (FGD), menjadi desain produk teruji internal tidak di uji lapangan. Hasil penelitian pendahuluan diperoleh visualisasi model faktual kepemimpinan Top Down dalam manajemen pembiayaan sekolah. Tahap pengembangan diperoleh hasil visualisasi model kepemimpinan transformasional dalam manajemen pembiayaan sekolah. Hasil validasi dan penilaian dari dua pakar pendidikan pada (FGD) diperoleh nilai 46 persentase 95,83% interpretasi “sangat layak”, sedangkan hasil validasi dan penilaian dari lima praktisi pendidikan diperoleh skor 101 persentase 84,16% interpretasi “sangat layak”. Maka Pakar 1 dan Pakar 2 menyetujui model kepemimpinan transformasional dalam manajemen pembiayaan sekolah “sangat layak” dan teruji. Kepala Sekolah sebaiknya mengimplementasikan model kepemimpinan transfomasional dalam manajemen pembiayaan sekolah agar terselenggara prinsip partisipasi, transparansi dan akuntabel.